2017
DOI: 10.17584/rcch.2017v11i2.7345
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de diferentes láminas de riego en el crecimiento y desarrollo de cebolla de bulbo (<i>Allium cepa</i> L.)

Abstract: Debido al sistema radicular superficial, la cebolla de bulbo requiere de un suministro de riego en el momento y con la intensidad adecuada para favorecer la absorción de agua y nutrientes y obtener altos rendimientos. Se evaluó el efecto de diferentes láminas de riego en el crecimiento y desarrollo de cebolla de bulbo en un suelo franco arenoso y con un sistema de riego por aspersión. Se usó un diseño experimental completamente al azar con cuatro tratamientos (coeficientes de cultivo de 0,8; 1,0; 1,2 y 1,4 de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Moisture sensors and 100% Evt developed better, reaching average values of 8.92 and 9 cm, higher than those found by Cargua, (2013), who reported equatorial diameter values of 7.42 and 7.20 cm per bulb for the Yellow granex variety, lower even than the diameters of 7.8 cm in 60 % Evt. -Herrera et al (2017) reported that the growth of bulb onions is sigmoidal, explaining the reduction of the polar diameter and increase of the equatorial diameter, with subsequent flattening related to the accumulation of photoassimilates during the bulbification stage. Kumar et al (2007) stated that water regimes greater than the evapotranspiration normally generate an increase in the polar diameter of bulb onions, even when the applications reach 150% Evt.…”
Section: Growth Of the Polar Diameter And Equatorial Diametermentioning
confidence: 99%
See 2 more Smart Citations
“…Moisture sensors and 100% Evt developed better, reaching average values of 8.92 and 9 cm, higher than those found by Cargua, (2013), who reported equatorial diameter values of 7.42 and 7.20 cm per bulb for the Yellow granex variety, lower even than the diameters of 7.8 cm in 60 % Evt. -Herrera et al (2017) reported that the growth of bulb onions is sigmoidal, explaining the reduction of the polar diameter and increase of the equatorial diameter, with subsequent flattening related to the accumulation of photoassimilates during the bulbification stage. Kumar et al (2007) stated that water regimes greater than the evapotranspiration normally generate an increase in the polar diameter of bulb onions, even when the applications reach 150% Evt.…”
Section: Growth Of the Polar Diameter And Equatorial Diametermentioning
confidence: 99%
“…An adequate supply of water in regimes that provide 80 to 100% Evt can impart adequate root and leaf growth values (Shao et al, 2008). Using smaller amounts of water, as with the moisture sensors, does not guarantee adequate root development, instead generating shorter and thicker roots and limiting the necessary amount of absorbed water because of a smaller surface area (Alvarez-Herrera et al 2017;Wakchaure et al, 2020). The treatment 150% Evt had the shortest root length (8.13 cm) because, when the soil has moisture saturation, gases such as O 2 and CO 2 diffuse more slowly, making them inaccessible to the roots.…”
Section: Leaf and Root Growthmentioning
confidence: 99%
See 1 more Smart Citation